Design And Build A Mobile-Based Daily Prayer Learning Application (Case Study: MTS Al Hidayah Limabangan) - Yopi Nugraha (Institut Pendidikan Indonesia, 2021)
The development of technology is currently growing rapidly and as we know in this day and age many junior high school students are using smartphones and used to commucate with their parents or just for play gamming. During the covid-19 pandemic, the use of smartphones by junior high school students is increasing due to the need for online learning activities from home. There are many kinds of daily prayer learning books but because junior high school students use their smartphones more often than reading books. With the creation of mobile-based daily prayer learning application, it is hoped that it can help junior high school students in learning daily prayers trough their smartphones which they can learn anywhere and anytime. The method used in the design of this application is using agile method. The results of this study are mobile-based daily prayer learning application designed to suit the needs of the MTS Al Hidayah Limbangan school in which there are daily prayers in arabic, latin of arabic written, and their meaning so that they can be easily understood.